2016
DOI: 10.1007/s11390-016-1630-x
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Simulation for Mobile Ad-Hoc Communication for Disaster Scenarios

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…Two Security methods processed under the process of executing, Integration Detection systems and Way-Sharing techniques [34]. The executable grid used to inspect is the access element and the accuracy factor.…”
Section: Related Workmentioning
confidence: 99%
“…Two Security methods processed under the process of executing, Integration Detection systems and Way-Sharing techniques [34]. The executable grid used to inspect is the access element and the accuracy factor.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, they showed that for major disasters there is a correlation between damage and social media activity. Other efforts have focused on communication infrastructure during earthquakes by providing methods to favor message sharing during disasters in mobile networks [23], providing access to spatio-temporal data during disasters [24], and testing communication infrastructure using simulated data [25]. Along this line, several text mining methods have been used to elaborate reports, providing event summarization [4] (a short textual description of the earthquake) or detecting local related events such as looting and pillage [26].…”
Section: Related Workmentioning
confidence: 99%
“…Every year, millions of people are affected by natural disasters such as earthquakes, tsunamis, volcano eruptions, hurricanes, tornados and floods, and governments all around the world spend huge amounts of resources on the reconstruction and the preparation for such calamities. In 2013 alone, 97 million victims were affected by 330 natural disasters and the economic damage amounted to 156.6 billion dollars (Rosas et al 2016).…”
Section: Emergency Management and Responsementioning
confidence: 99%